Autism Spectrum Disorders (ASD) and Health Care Services for Underserved Populations - Petinou, Kakia; Christopoulou, Maria (My University, 2022)
This chapter presents key information related to Autistic Spectrum Disorders (ASD) for the attention of National Policy Members, stakeholders, lawmakers, and healthcare professionals. We set out to encourage the fostering and advocacy for greater health literacy pertinent to ASD. In our opinion, it is of particular importance to advance the knowledge on issues related to prevalence, early symptomatology, diagnostic characteristic etiology, aberrant behaviours, daily living challenges, disorders of verbal and nonverbal communication, schooling adaptation, social pragmatic deficits, and difficulties related to emotional affect. An increased awareness on these topics is paramount as awareness, particularly on early detection of symptoms, can lead to timely assessment and diagnosis. Early detection of ASD signs and early diagnosis through an interdisciplinary management programme contributes to positive therapy outcomes (Koegel & Koegel, 1995; Petinou & Minaidou, 2017; Rapin, et al., 2009; Richard, 1997). A recent publication by the Centers for Disease Control and Prevention (CDC, 2020) reports significant progress for early ASD screening resulting from rigorous research investigations and systematic ASD awareness campaigns over the past ten years. These efforts have capitalized on the available data and allow the fostering of ASD awareness. Robust advocacy for ASD has been undertaken by the NGO organizations including Autism Speaks (2016) and Ad Council. Increased screening has contributed to the lowering of the age of diagnosis, especially in minority populations and in individuals with diverse cultural and linguistic backgrounds. A recent report by the World Health Organization (WHO, 2019) underscores the importance of implementing integrated services in accordance with the person’s individual needs and preferences. People with ASD do not differ from the rest of the population when it comes to health problems. Nevertheless, their special needs and co-occurring conditions necessitate awareness from politicians supported by committees who can address the societal needs and the level of support to increase the quality of life, access to services, family support and availability to resources of best service provision according to the Declaration of Human Rights (DHR) (United Nations, 1948).